RECRUITMENT TENAGA KERJA HOUSEKEEPING DEPARTMENT DI SIJORI RESORT & SPA BATAM - Siregar, Derinda Al Faizah; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Sijori Resort & SPA Batam in determining the recruitment process of employees are more concerned with the knowledge and skills of applicants compared to the education is owned by the applicants, so that they get prospective qualified workers. Because Sijori Resort & SPA Batam is four star resort, so that housekeeping staff must have a knowledge and skill in cleaning and makeup room, these skills are needed to get a competent and professional housekeeping staff compared another hotels in Batam. The purpose of this research is to know how Sijori Resort & SPA Batam on determining of recruitment process of housekeeping staff and the problems happen when the recruitment is processed, and effort the problem solve when do the recruitment process. This research use qualitative methods with descriptive approach. and the indicators are basic of recruitment, source of recruitment, methods of recruitment, and the obstacles of recruitment. Data is obtain form deep interview with human resources manager and housekeeping supervisor, other than that equipped amplifier data with the checklist form for housekeeping staff, direct observation and documentation. Then data that has been obtained, is analyzed using three steps: reduction data, display data and verification. The result of this research is shows that Sijori Resort & SPA Batam doing recruitment process has apply some criteria from the indicator that has been specified based on the results of the respondent's answers. Key Words: Recruitment, Housekeeping Department, Sijori Resort & SPA Batam